-9=6(w+5)

Simple and best practice solution for -9=6(w+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=6(w+5) equation:



-9=6(w+5)
We move all terms to the left:
-9-(6(w+5))=0
We calculate terms in parentheses: -(6(w+5)), so:
6(w+5)
We multiply parentheses
6w+30
Back to the equation:
-(6w+30)
We get rid of parentheses
-6w-30-9=0
We add all the numbers together, and all the variables
-6w-39=0
We move all terms containing w to the left, all other terms to the right
-6w=39
w=39/-6
w=-6+1/2

See similar equations:

| 5x+22=12x | | 9/25=x/30 | | n=9+-1.7763568394003E-15/1.56 | | 10-5x=49 | | 3x+2=6x−5 | | 4(2x-9)-6x=34 | | 4-7=x-10 | | 28=-32+12n | | (2x-9)-6x=34 | | 30m+75=435 | | 3=2k+12 | | x+2x^2+3x+2=180 | | 5a=155 | | 18=5h-2= | | 1.56(n-6)-1=3.68 | | 75m+30=435 | | 27x=3(10x+1) | | 143=(5x+13) | | 18x+12=8x+2 | | (x-15)+43=180 | | 4-2m=m+10 | | –1+–6y=53 | | 10s=-4(-2s+7)+10 | | 3(x+1)+2X=8X+3-3X | | 5+v/5=-25 | | 6x+9=14x-7 | | 6u+3u=8 | | 172=4(7x-6) | | 5y-1=3y+29 | | 15+2t=21 | | 8x+4x-5x=28 | | (4+3x)/2=5 |

Equations solver categories